Найдите:
y=cos5xcos8x; y( frac{ pi }{6} )=?

y=cos5x*cos8xy=-sin5x*(5x)*cos8x-sin(8x)*(8x)*cos5x==-(5sin5x*cos8x+8cos5x*sin8x)y(frac{pi}6)=-(5sin(5*frac{pi}6)*cos(8*frac{pi}6)+8cos(5*frac{pi}6)*sin(8*frac{pi}6))==-(5sin(frac{5pi}6)*cos(frac{4pi}3)+8cos(frac{5pi}6)*sin(frac{4pi}3))==-(5*frac{1}2*(-frac{1}2)+8*(-frac{sqrt3}2)*(-frac{sqrt3}2))=frac{5}4-frac{8*3}4=-frac{19}4

Оцени ответ
Подпишись на наш канал в телеграм. Там мы даём ещё больше полезной информации для школьников!

Загрузить картинку
×